Politics, Economy and Islam in ‘Dutch Ponnāni’, Malabar Coast - Kooria, Mahmood (Journal of the economic and social history of the Orient, 2019)
Abstract Ponnāni was a port in southwestern India that resisted the Portuguese incursions in the sixteenth century through the active involvement of religious, mercantile and military elites. In the late seventeenth and eighteenth centuries Ponnāni was the only place where the Dutch East India Company had commercial access into the kingdom of the Zamorins of Calicut. When the Dutch gained prominence in the coastal belt, this port town became the main centre for their commercial, diplomatic, and political transactions. But as a religious centre it began to recede into oblivion in the larger Indian Ocean and Islamic scholarly networks. The present article examines this dual process and suggests important reasons for the transformations. It argues that the port town became crucial for diplomatic and economic interests of the Dutch East India Company and the Zamorins, whereas its Muslim population became more parochial as they engaged with themselves than with the larger socio-political and scholarly networks.